Enhancing Learning Motivation and Learning Outcomes through an Online Game-Assisted Teams Games Tournament (TGT) Cooperative Learning Model in Arabic Morphology Learning - Intan Afriati; Nauwal aufa; Sri Wahyuni Hidayanti; Naufir Raudhatiz Zayyan; Nurrahma Wati (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study aims to determine the effectiveness of the Teams Games Tournament (TGT) cooperative learning model assisted by online games in improving students' motivation and learning outcomes in sharaf (Arabic morphology) course material. This research was initiated by students' low motivation and difficulties in understanding word inflection patterns due to teacher-centered learning. A quantitative approach with a pre-experimental one-group pretest-posttest design was employed. The research subjects consisted of 11 eighth-grade students at MTsS Inshafuddin, Banda Aceh. Data collection techniques included learning outcomes tests and motivation questionnaires, which were analyzed using the Shapiro-Wilk normality test and the paired sample t-test. The results showed a significant increase in learning outcomes, with the average score increasing from 64.3 to 85.1, or by 32.3%. The hypothesis testing revealed a significance value of < 0.05, indicating a significant difference between the pretest and posttest scores. Furthermore, student responses showed an average percentage of 92%, falling into the highly positive category. Therefore, the online game-based TGT model is effective in improving students' learning outcomes and motivation in learning sharaf.